Integrated palliative care in Europe: a qualitative systematic literature review of empirically-tested models in cancer and chronic disease. Issue 1 (December 2016) - Siouta, Naouma; Van Beek, K.; van der Eerden, M.; Preston, N.; Hasselaar, J.; Hughes, S.; Garralda, E.; Centeno, C.; Csikos, A.; Groot, M.; Radbruch, L.; Payne, S.; et al.
Abstract Background Integrated Palliative Care (PC) strategies are often implemented following models, namely standardized designs that provide frameworks for the organization of care for people with a progressive life-threatening illness and/or for their (in)formal caregivers. The aim of this qualitative systematic review is to identify empirically-evaluated models of PC in cancer and chronic disease in Europe. Further, develop a generic framework that will consist of the basis for the design of future models for integrated PC in Europe. Methods Cochrane, PubMed, EMBASE, CINAHL, AMED, BNI, Web of Science, NHS Evidence. Five journals and references from included studies were hand-searched. Two reviewers screened the search results. Studies with adult patients with advanced cancer/chronic disease from 1995 to 2013 in Europe, in English, French, German, Dutch, Hungarian or Spanish were included. A narrative synthesis was used. Results 14 studies were included, 7 models for chronic disease, 4 for integrated care in oncology, 2 for both cancer and chronic disease and 2 for end-of-life pathways. The results show a strong agreement on the benefits of the involvement of a PC multidisciplinary team: better symptom control, less caregiver burden, improvement in continuity and coordination of care, fewer admissions, cost effectiveness and patients dying in their preferred place. Conclusion Based on our findings, a generic framework for integrated PC in cancer and chronic disease is proposed. This framework fosters integration of PC in the disease trajectory concurrently with treatment and identifies the importance of employing a PC-trained multidisciplinary team with a threefold focus: treatment, consulting and training.